Motivation: The Road to Successful Learning (2015)
This research has the aim of highlighting the importance of motivation in the process of learning English as a foreign language. For that purpose, some factors that affect motivation are described, using as a starting point the answers obtained from a questionnaire given to students in their fourth year of compulsory secondary education. The main conclusions of the research show the fundamental role of factors such as the teacher, the four skills, students’ interests and daily habits, among others. Finally, some guidelines for a teaching methodology are proposed with the intention of future development.Esta investigación nace con el objetivo de resaltar la importancia de la motivación en el proceso de aprender inglés como lengua extranjera basándose en los resultados obtenidos en un cuestionario para alumnos de cuarto curso de Educación Secundaria Obligatoria. Las principales conclusiones de la investigación muestran el papel fundamental que juegan algunos de los factores que afectan a la motivación como el profesor, las cuatro destrezas, los intereses y hábitos de estudio de los alumnos, etc. En la parte final de la investigación se describe una serie de pautas para desarrollar una propuesta metodológica que tenga en cuenta los resultados de este estudio.